PENDEKATAN KOMUNIKASI ANTARBUDAYA HAKIM DI PENGADILAN AGAMA BENGKULU - Robeet Thadi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2021)
The purpose of this study was to reveal how the process and approach to intercultural communication of non-Bengkulu ethnic judges at the Religious Courts Class 1 A Bengkulu in handling divorce cases. This study uses a qualitative approach to the tradition of symbolic interactionism, data was collected using participant observation, in-depth interviews, and documentation studies. With purposive sampling technique, 4 judges and 2 clients became research informants. The results showed that the communication process in PA Bengkulu occurred between several different ethnicities, especially in the trial and mediation processes, such as differences in language and culture. “Mediation Room” is the dominant interaction in the intercultural communication process between judges and clients/parties in the proceedings. Although the results of the study show that the contribution of the mediation space in reconciling clients is still very limited. The communication process takes place in an interactional way with a dialogic/dialectical approach. The dialectical approach was used by the judges at PA Class 1 A Bengkulu to facilitate communication that took place especially at the beginning of the trial and mediation time.